The Review of the PRS (Pre-Raphaelite Society). (Birmingham : Pre-Raphaelite Society, 1993)
The Review is the Society’s principal publication, published three times a year and dated Spring, Summer and Autumn. The publication contains articles, book reviews, illustrations and 'Notes and Queries', and offers the opportunity for all members who are interested in research and writing to contribute in a very satisfying way to the Society’s life (www.pre-raphaelitesociety.org/about-the-prs-review)
Https://www.pre-raphaelitesociety.org/about-the-prs-review.html
Engels
Tijdschriften
Keywords: prerafaëlieten